ANALISIS MORFOLOGIS FI‘IL MUJARRAD DAN FI‘IL MAZĪD BI ḤARFIN DALAM SURAT AL-KAHFI - Lutfiana Sefira (Jurnal Eduslamic, 2025)
This study aims to analyze the forms of verbs in Surah Al-Kahfi Ayat 9–26, especially in the story of Ashḥābul Kahfi, through a morphological approach (ṣarf) using a qualitative literature study method. The main focus of the study is to classify and study in depth the verbs of tsulāthī mujarrad and mazīd bi ḥarfin, and to explain their functions and meaning tendencies in the context of the Ayat. In the analysis process, each verb is reviewed in terms of madī and muḍāri‘ forms, wazan patterns, basic or additional meanings, and their relationship to the meaning of the Ayat as a whole. The results of the study show that the verbs of tsulāthī mujarrad tend to be used to describe the direct actions of the young men of Ashḥābul Kahfi, such as talking, walking, or sleeping. Meanwhile, the verbs of mazīd bi ḥarfin appear more often in the context of Allah's intervention or power, such as giving instructions, revealing events, or recording information. This finding reveals how the choice of the form of the fi’il in the Qur’an has a significant semantic and rhetorical role, and shows the richness of the structure and economy of the Arabic language. This analysis is expected to broaden scientific insight in the field of Qur’anic linguistics and contribute to Arabic morphological studies, especially in understanding the structure of fi’il derived from the sacred text.